A leitura literária e a formação do leitor proficiente - Vildete Gomes Pereira (2019)
The dissertation aims to describe and analyze a teaching practice of literary reading in the classroom. The proposal was developed and applied in a 6th grade class of the State School "Juscelino Kubitschek de Oliveira" in the municipality of Ibirité, Minas Gerais. The focus of the practice was to provide literary reading in the classroom in order to contribute to the formation of a proficient reader.